DAUGHTERS’ AMBITION IN WILLIAM SHAKEPEARE’S KING LEAR - Karli Kambey; Fivy A. Andries; Merlin M. Maukar (Program Studi Pendidikan Bahasa Inggris, 2022)
The purpose of this study is to reveal the cruel nature and ambition of the two daughters of King Lear (Goneril and Regan) King Lear is one of the works of Author William Shakespeare's, a famous story during the time of Queen Elizabeth II. This research is categorized as qualitative research because the data collected from several articles, journals, searches from the internet. And in analyzing the data the writer uses a psychological approach because this includes human behavior, both individuals and groups who do harmful behavior and even benefit themselves, ethnicity, nation, society, government, religion, or organization. So, this drama explains how their actions have affected the lives of those around them, even physically and mentally damaging King Lear, even themselves. This triggers the ambition to move forward to get desires and desires that result in destruction, even death, so that the lives of brothers and sisters finally break apart, conflicts occur because of the ambition to have power and get love so that one by one die, without justice.